Strategy shelved the collapse of Cold War naval strategic planning - Wills, Steven (Naval Institute Press, 2021)
"Strategy Shelved examines the rise and eventual fall of the U.S. Navy's Cold War era naval strategy system from the immediate post-World War II era to 1994. It focuses on the 1970s and 1980s as a period when U.S. naval strategic thought and creation was rebuilt after a period of stagnation during the Vietnam conflict and its high watermark in the form of the 1980s Maritime Strategy and its attendant 600 ship navy force structure"--